If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 1) + -20 = 2(y + -5) Reorder the terms: 3(1 + y) + -20 = 2(y + -5) (1 * 3 + y * 3) + -20 = 2(y + -5) (3 + 3y) + -20 = 2(y + -5) Reorder the terms: 3 + -20 + 3y = 2(y + -5) Combine like terms: 3 + -20 = -17 -17 + 3y = 2(y + -5) Reorder the terms: -17 + 3y = 2(-5 + y) -17 + 3y = (-5 * 2 + y * 2) -17 + 3y = (-10 + 2y) Solving -17 + 3y = -10 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -17 + 3y + -2y = -10 + 2y + -2y Combine like terms: 3y + -2y = 1y -17 + 1y = -10 + 2y + -2y Combine like terms: 2y + -2y = 0 -17 + 1y = -10 + 0 -17 + 1y = -10 Add '17' to each side of the equation. -17 + 17 + 1y = -10 + 17 Combine like terms: -17 + 17 = 0 0 + 1y = -10 + 17 1y = -10 + 17 Combine like terms: -10 + 17 = 7 1y = 7 Divide each side by '1'. y = 7 Simplifying y = 7
| d+21=36 | | 10s+4=-5+9s | | (X-4)(3x+5)= | | Y(C+d)+n(c+d)= | | 4(x-3)=8-2(x+4) | | 17-x^2=0 | | -4u+7=-5u | | .85=y/20 | | m+9=25 | | x^2+3-6-4x= | | x*lnx+(x-1)*ln(x-1)=0 | | .85=?/20 | | 6c+10=-5+9c | | 2x^2-6x+8=x^2+3x | | 11x^2+5x-7+6y= | | 7x=-7y+14 | | 3x-20=30x | | 20CD= | | 3(15-n)=36 | | 16+w=22 | | -6k-5=-4K+7 | | 5(5-m)=3(m+1) | | 4.9t^2+19.6t-14.7=0 | | -6d=6-5d | | 3x+30=y+10 | | -4x^2=8x+5 | | 46+f=81 | | 4x/5=9 | | .35x-.45(x-2)=4.4 | | z+8.009=10 | | 6-9h=-8h | | 33+d=67 |